Komunikasi Instrumental Gerakan Bela Beli Kulon Progo dalam Membangun Regional Branding - Alvian Alrasid Ajibulloh; Chandra Putra Adi Prayoga (Jurnal Riset Komunikasi, 2022)
This article examines the implementation of instrumental communication in the Kulon Progo Bela Beli movement in establishing regional branding and what actions the Kulon Progo Regency Government has taken to make the campaign successful. This study uses a descriptive qualitative method with an instrumental theoretical approach to the model of persuasion and the concept of regional branding. The data sources of this research involve several sources; Kulon Progo district government officials and community leaders. The results show that the Bela Beli Kulon Progo movement uses various approaches to persuade the public and several regional branding concepts to make the Bela Beli Kulon Progo movement a regional branding. So that the Bela Beli Kulon Progo movement has succeeded in encouraging significant economic growth and reducing the percentage of poverty in the Kulon Progo Regency Government from year to year. The people of Kulon Progo are also increasingly appreciating and buying local Kulon Progo products by producing, marketing, and buying Kulon Progo products.